First investigation on the photophysical and photochemical properties of azo-bridged phthalocyanine photosensitizers - ALTUN, SELÇUK; ODABAŞ, ZAFER (ELSEVIER SCIENCE BV, 2016)
Novel azo-bridged indium(III) acetate phthalocyanine was synthesized by cyclotetramerization reaction of (E)-4-((2,5-dimethoxyphenyl)diazenyl)phthalonitrile. This phthalocyanine was fully characterized by FT-IR, H-1-NMR, UV-vis and MALDI-TOF mass spectroscopic techniques and elemental analyses as well. Additionally, the photophysical and photochemical properties of this phthalocyanine was investigated for the first time. The obtained results were compared with azo-bridged zinc(II) and metal-free phthalocyanine counterparts for determination of central metal effect on these properties. These results were also compared with unsubstituted zinc(II) and indium(III)acetate phthalocyanines for determination of substitution effect on the photophysical and photochemical properties. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Dimethoxyphenoxy; Indium(III)acetate phthalocyanine; Azo-bridged; Fluorescence; Singlet oxygen; PHOTODYNAMIC THERAPY; INDIUM PHTHALOCYANINES; METAL PHTHALOCYANINES; ZINC PHTHALOCYANINE; SUBSTITUENTS; DERIVATIVES; SENSORS; HYDROGEN; BEHAVIOR; CHLORIDE